"Variae Medeae": a recepção da 'fabula' de Medeia pela literatura latina: a recepção da fabula de Medeia pela literatura latina - Marcio Meirelles Gouvea Junior (2013)
Medea, the witch who saved the Argonauts from dangers of the East and brought ruin and death to the Greek cities, arrived in Rome, around the third century BC, as one of the many fabulae which belonged to the vast mythological Hellenistic repository, welcomed during the insertion process of the Vrbs into the cultural world which had been amalgamated by Alexanders conquests. At that point, the long journey of the artistic tradition of her narrative started, a journey which exceeded the chronological dimension of Latin paganism, to achieve, at the beginning of the sixth century AD, the latinitas coming from Christianized Northern Africa. Along the way, her condition was always the one of a literary matter, subject of poets, as Cicero points out: poetarum ista sunt(CIC. N.D. 3.77). Thus, summarizing the countless variants and versions of the myths that dealt with the history of the Colchian princess in Greek context, her character was unified in Latin scope in the concise determination of Horace (Hor. Ars. 123): Medea ferox sit inuitaque: Let Medea be fierce and invincible. The attributes of this foreign witch, however, gave authors the faculty for reflecting on one of the problems that the inhabitants of Rome and its domains faced out very frequently: dealing with barbarism. However, Medea did not represent a kind of barbarism which could be defeated and subdued to Roman culture, but that indomitable one over which it was impossible to win a victory, the one which, ultimately, by contrast, would define the boundaries of the Roman State and the own subjectivity of the uir romanus. Thus, the comparative analysis of the Variae Medeae carried out through interpretation of the references to the plot of the Latin poets of the witch from Colchis in Latin poets, and th rough references to the speeches of the oratores and the use of pictorial records of her tragic episodes, leads to reflection and enlargement of the understanding of the phenomenon of barbarism itself at the present time, as it was understood by the ancient Romans. Through the extraction of the concept of barbarus from each of the works which referred to Medea, it was determined, in the course of Roman history, who the barbarians were, which fundamental features they had and what kind of dangers they constituted to the Vrbs and the romanus. Therefore, by analyzing the literary reception of the fabula Medeae Romae, it was possible to deepen the concept itself of being Roman.